Investigation of Anxiety among Pharmacy Students during the COVID-19 Pandemic in Northern Cyprus - Hamurtekin, Emre; Bosnak, Ahmet Sami; Farhoumand, Forouzandeh; Mohebali, Azadeh; Kaymak, Aysegul; Motaghinejad, Majid (Dubai Iranian Hosp, 2022)
Background: Anxiety is common among university students and previous research has highlighted the association between the COVID-19 pandemic and higher anxiety scores in the public. Objectives: In this regard, this study aimed to evaluate the effect of the COVID-19 pandemic on the anxiety status of pharmacy students studying in Northern Cyprus and analyze the role of some parameters on the observed anxiety scores. Methods: Anxiety scores of 185 pharmacy students studying at two universities in Northern Cyprus were evaluated using Beck Anxiety Inventory (BAI) and Generalized Anxiety Disorder-7 (GAD-7) assessments. Additionally, the information of participants was recorded in terms of sociodemographic and educational characteristics, antidepressants and anxiolytic use, and consumption of vitamin-mineral supplements. The questionnaires were distributed during the COVID-19 pandemic from December 11, 2020, to January 4, 2021, online via the Microsoft Teams (R) platform. It should be mentioned that responses were anonymous. Results: The mean BAI and GAD-7 scores of pharmacy students were 13.1 +/- 11.2 and 10 +/- 6.7, respectively. Based on the results, 6% of the students (n=11) revealed potentially concerning levels of anxiety in their BAI responses. Moreover, 31.9% of the pharmacy students (n=59) demonstrated severe anxiety scores on the GAD-7. Positive COVID-19 cases in the family led to statistically significant increases in anxiety on both instruments. Pharmacy students with five years of education (B.Pharm/M.Pharm) showed significantly higher anxiety scores on the BAI. Besides, age correlated negatively with anxiety scores on the GAD-7. Neither antidepressant and anxiolytic use nor vitamin/mineral supplement use were not related to the anxiety scores of participants. Conclusion: Results of this study demonstrated an alarming anxiety status among pharmacy students during the COVID-19 pandemic period. Diagnosis of a family member with COVID-19 was observed to be critical in triggering the anxiety of pharmacy students. Data from this study should raise awareness to take action plans for the mental well-being of pharmacy students during pandemics.
Keywords: Anxiety; COVID-19; Pharmacy; Students